The influence of Using Martha Christina Tiahahu Struggle History Module on History Awareness of Muhammadiyah High School Students Raha - Leni Marpelina; Resmiyati Yunus; Andris K Malae (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2022)
This study aims to describe the effect of using the Martha Christina Tiahahu Struggle History Module on the historical awareness of Muhammadiyah Raha High School students. The subjects in this study were 60 students of class XI SMA Muhammadiyah Raha. This research was an experimental study using the experimental class (history module) and the control class (regular textbook). The objects of this research are students of class XI SMA Muhammadiyah Raha in the academic year 2019/2020. The results showed that the regression coefficient value of the history module (X) was 0.360 with a significance level of 0.001 < 0.005 while the F value was found to be 9.206 with a significance level of 0.001. and the value of R2 (R Square) was found to be 0.627 which means that the independent variable, namely the history module, affects the student's historical awareness variable by 62.7%, while the remaining 30.73% is a unique factor that cannot be investigated in this study. Thus, it can be concluded that the struggle history module of Martha Christina Tiahahu (X) affects the historical awareness of the students of SMA Muhammadiyah Raha.